Interactive Media in English Vocabulary Instruction: Types and Pedagogical Challenges - Syamsinar; Mulyani, Mulyani; Kamariah, A.; Afdaliah, Nihla (Universitas Sulawesi Barat, 2025)
Nowadays, the use of learning media has essential role in teaching. The lecturer should use interesting media to attract the students’ attention. The media should be innovative and interactive especially in teaching English vocabulary. The objective of the study was to find out the types and challenges of various interactive media in teaching English vocabulary. The subject of the research was the first semester students of English Education at STAIN Majene. The instruments were classroom observation and interview. This research used qualitative research. The data were collected by using lecturer’s interview, observation sheet for students and lecturer. The data were analyzed in four stages namely data collection, data display, data condensation and conclusion drawing. The result of the research showed that the lecturer used 4 types of Interactive media in form of interactive quiz, video, books, and flash card The implementation of various media was interesting and attracts the students’ attention. The students were active to take a part in learning because the medias were interactive. The students were more active than the use of textbook. Besides, there were some challenges in implementing the media. They are limitations of technological devices, time constraints in preparation, resistance of users, distraction of students’ focus, and irrelevant of Instructional materials and media.